BILINGUISM - LANGUAGE AND CULTURAL ADAPTATION - Omanov Pulatjon Khabitovich (American Journals, 2024)
In today's globalization era, the expansion of socio-economic and cultural relations between peoples and states has turned the issues of bilingualism and multilingualism into one of the important sociolinguistic factors in the development of society. The increasing phenomenon of bilingualism and multilingualism in the relationship between language and society, and the problems of communicative and cognitive development of monolingual and multilingual individuals, highlight the importance and urgency of language education and the necessity to conduct extensive research on these issues. This is explained by the need to understand the process of how multiple languages function in individuals, the impact of multilingualism on brain activity, and the cultural relations among multilinguals, which have not yet been fully studied.
Keywords: Socio-cultural approach bilingualism, plurilingualism, multilingual education, socio-cultural approach, secondary linguistic identity, plurilingualism